On the demand to incorporate Shari'a law into UK law - Serageldin, Mayada (AUC Knowledge Fountain, 2013)
The origin of this thesis lay in the emergence of a minority group of ‘religious’ activists in London, England. The purpose of this group was to establish “Shari’a Zones” in pockets of Waltham Forest and Tower Hamlets, wherein certain acts would be prohibited and Shari’a law would be enforced. This led to an examination of the theological and religious beliefs of this small and much marginalized section of the British Muslim community. What became apparent is that this group prescribed to a view of Islam, and shariah law in particular, which is incongruent with the provisions of human rights law. In complete contrast, as this thesis will explain, there are other interpretations of Shari’a law that are more complimentary to the tenets of human rights and civil liberties on which British society is based. This assertion should underscore how the principles of equality and justice are intrinsic to the Islamic faith.Having identified the above divergence in the representation of Islam by this sub-strata of British Muslims, this thesis will consider the British system within which this group and other Muslims operate. This is primarily done to get a general idea about how British Muslims are allowed and tolerated, by the system, to be as such. The conclusion reached is that these particular Muslims are not just portraying in inaccurate image of British Muslims, but they may well be practicing their religion wrongly. Thus, their conduct is counter-productive and their purpose is self-defeating.